The Treasures of Renal Isle: Evaluating a Gamified Module While Enhancing Student Learning - Shinu Joy DNP, MSN, RN, NPD-BC, OCN; Kimberly Rumsey DNP, RN, CNE; Meredith Ford PhD, MSN, RN, CNE (SAGE Publishing, 2024)
Introduction Nursing education continues to evolve with the integration of innovative technologies aimed at enhancing student engagement and understanding of complex medical concepts. Gamification, the application of game elements in nongame contexts, emerges as a promising tool in nursing education. Method Faculty members collaborated with instructional designers to develop, The Treasures of the Renal Isles , a gamified module for nursing education. Drawing upon their expertise, faculty provided content knowledge and identified key gaming elements, while designers crafted a virtual world and storyline to contextualize the learning experience. The module was implemented within the curriculum, and student feedback was solicited through the Gameful Experience Scale (GAMEX), a validated tool for assessing gamified learning experiences. Additionally, exam scores were analyzed to determine the gamified module's impact on learning outcomes. Results Analysis of student responses to the GAMEX tool revealed favorable perceptions of the gamified renal module. Specifically, 77.3% of students believed that the module facilitated their understanding of renal content, indicating its efficacy in knowledge acquisition. Moreover, 71% of students expressed a desire for additional gamified modules, highlighting their engagement and interest in this instructional approach. However, despite positive feedback, no significant differences in test scores were observed postimplementation. Conclusion The findings of this project highlight the potential of gamification as an interactive learning method in nursing education. While the gamified renal module received positive feedback from students regarding its effectiveness in facilitating understanding, the lack of significant improvement in test scores warrants further refinement. By incorporating student feedback and revising the module accordingly, nursing educators can utilize gamification to bridge the gap between theoretical knowledge and clinical judgment. The development of additional gamified modules holds promise for enriching the learning experience and preparing nursing students for the complexities of clinical practice.